PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN SIKAP PARA GURU TERHADAP KEPUASAN KERJA (Studi kasus di MA PALAPA NUSANTARA NW SELEBUNG) - Asbullah Muslim (CENDEKIA: Jurnal Studi Keislaman, 2015)
This study aims to determine the effect of the principal leadership and the teacher’s Attitude toward job satisfaction in MA Palapa Nusantara NW Selebung. Leadership is the ability of a school principal in influence and mobilize subordinates in an organization or school institutions in order to achieve school goals. Attitude of teachers to work is a teacher’s tendency to respond his pleasure or displeasure to his job. Teacher’s job satisfaction is a delightful emotional state that is owned by teacher. The data obtained from the School is analyzed using SPSS in phases: Preparation, Test and SPSS Analysis. Through the research can be concluded that there is a relationship between the principal leadership and teacher’s performance with job satisfaction.